Histological and immunohistochemical study on granular cell trichoblastoma - Sharif, M.; Reinacher, M. (Al-Mukhtar Journal of Sciences, 2011)
A granular cell trichoblastoma was found at the auricle of a 10 years old, male Epagneul dog. Histolologically, two distinct types of neoplastic cells were present, basaloid and granular cells. Immunohistologically, the tumor cells were positive for Cytokeratin and negative for Vimentin, Lysozyme and S100.